Cognitive processes in parametric design: A systematic literature review of methods, models, and future directions - Er, Ihsan Erdem; Arabacioglu, Feride Pinar; Tastan, Hasan (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2025)
This study explores cognitive processes in parametric design environments (PDEs), synthesizing current research to identify key methodologies, theoretical models, and factors that influence design cognition. The review addresses challenges like cognitive overload, algorithmic dependence, and the learning gap between novice and expert designers. A systematic literature review (SLR), following PRISMA guidelines for transparency and reproducibility, was conducted to analyze studies on design cognition in PDEs, with a focus on empirical research examining cognitive processes, design behavior, and educational strategies. The review reveals that PDEs encourage creativity, iterative problem-solving, and dynamic design exploration but also pose cognitive challenges, particularly for inexperienced designers. Expert designers exhibit greater algorithmic fluency and adaptability, while novices often experience cognitive strain and reliance on black-box thinking, which limits their creative engagement. Educational gaps persist, highlighting the need for scaffolded learning models, hands-on workshops, and non-digital exercises to build algorithmic skills progressively. Additionally, the lack of standardized frameworks for evaluating algorithm quality and cognitive performance underscores the need for further research. This review provides insights for educators and researchers to bridge the gap between technical proficiency and creative innovation in parametric design.
Keywords: Cognitive processes; design cognition; parametric design; parametric design environment; systematic literature review; CREATIVITY; PATTERNS; Architecture